The mirror class as a multi-campus teaching and learning experience (2020)
Mirrors and Minds" was a multi-campus teaching initiative that led to the planning and implementation of a mirror class between two of the 18 UCC campuses in the country. According to ITM (2018), “ a mirror class is an academic resource that uses a digital platform shared between professors and students from two or more universities, to participate in the synchronous and asynchronous development of a complete course or a session of a course”. This teaching and learning experience was envisioned as an activity to be divided into two different sessions. This activity had to reflect the main characteristics of a blended learning model that combines virtual and face-to-face instruction and that, as Bartolome (2004) explains, helps students develop skills such as finding relevant information online, developing assessment criteria to curate content, using information to create new content and apply it in real situations, as well as in making individual and group decisions. Besides that, the lesson plan had to ensure that students would have an active role during the whole mirror class. In other words, the teachers would not use technology to just transfer knowledge to their students as done in more traditional teaching approaches. Since both campuses have American teaching assistants, it was decided that they would also participate in the activities planned by the teachers. Additionally, students would carry out and present, simultaneously, a collaborative teamwork project with their peers from the other campus. In order to ensure the acquisition and application of digital skills, the students had to use an online tool they had never used before in order to make and present their final project.